Spontaneous angina bullosa hemorrhagica of tongue: An unusual problem following prosthodontic procedure - Sachdeva, Suresh Kumar; Sachdeva, Ashwani; Sachdeva, Swati Saggar; Galav, Ashok (Padjadjaran Journal of Dentistry, 2017)
Introduction: Angina Bullosa Hemorrhagica (ABH) is the term used to describe benign subepitilial oral mucosal blood filled blisters, which are not attributed to any systemic disorder. It is a very uncommon condition, mostly seen in elderly patients. The exact etiopathogenesis of the ABH is not known. Herewith, we present a case of 50-year-old male patient who developed ABH on right lateral border of the tongue, following prosthodontics impression making for completely edentulous mouth. Methods: The case management method was topical application of chlorhexidine gel (1%) and lignocaine gel (2%) with avoidance of hot and spicy food. Result and discussion: After one week in treating with topical therapy, the lesion became normal.Â  The diagnosis of ABH is difficult in patients because of its asymptomatic nature. The early diagnosis of the lesion is very important as a rapidly expanding blood-filled bulla in the oropharynx can cause upper airway obstruction. Therefore, a high level of suspicion is warranted on part of dentists who may the first to encounter the lesion.Â  Conclusion: Spontaneous Angina Bullosa Hemorrhagica of tongue was an unusual problem that can occur following prosthodontic procedure. The management of the lession were intended to reduce pain or discomfort and prevent secondary infections.